2020
DOI: 10.1111/den.13890
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future perspective of artificial intelligence applications in endoscopic diagnosis and management of gastric cancer

Abstract: Image recognition using artificial intelligence (AI) has progressed significantly due to innovative technologies such as machine learning and deep learning. In the field of gastric cancer (GC) management, research on AI-based diagnosis such as anatomical classification of endoscopic images, diagnosis of Helicobacter pylori infection, and detection and qualitative diagnosis of GC is being conducted, and an accuracy equivalent to that of physicians has been reported. It is expected that AI will soon be introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…These techniques are now being applied to gastrointestinal endoscopy worldwide. AI has high diagnostic accuracy for esophageal, gastric, and colorectal cancers 16–18 . However, AI has been mostly used to identify irregular or malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques are now being applied to gastrointestinal endoscopy worldwide. AI has high diagnostic accuracy for esophageal, gastric, and colorectal cancers 16–18 . However, AI has been mostly used to identify irregular or malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…AI has high diagnostic accuracy for esophageal, gastric, and colorectal cancers. 16 , 17 , 18 However, AI has been mostly used to identify irregular or malignant lesions. Qualitative investigations for a comprehensive diagnosis to facilitate appropriate therapy remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, as mentioned earlier, Hirasawa et al [12] also reported a retrospective RCT, in which the CNN system showed ability to process endoscopic images with a decent diagnostic ability. As an attempt to compare the diagnostic ability of the system, the same group of authors conducted a test to compare it with expert endoscopists [32].…”
Section: Detectionmentioning
confidence: 99%
“…In the deep learning structure, if the parameters of the structure are too many and the training samples are too few, over fitting is a common problem in trained models [37]. The phenomenon of over fitting could appear in neural network training, which is shown in the following aspects [38]: the structure has small loss function and high prediction accuracy in the training data. However, contrary to the results obtained from the training data, the model has large loss function and low prediction accuracy.…”
Section: Dropoutmentioning
confidence: 99%